Banks Merger in India: Impact on Indian Banking: The Impact of Banks Merger on Indian Banking Sector (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The process of merger and acquisition of small and weak banks into strong banks is not new to India. It dates back to 1960s when some weak banks were m. erged into financially sound banks. The survey conducted so far shows that most of the mergers have been successful. On August 30, 2019 the Finance Minister of India Nirmala Sitharaman announced the merger of Banks focusing for development of global level financially strong Public sector banks in India. The Finance Minister declared the Government plan to merge 10 public sector banks into four large banks. After the mergers, there will be 12 public sector banks in India, including State Bank of India as the biggest commercial bank and Bank of Baroda next to it. The government is planning to create 6 to 7 strong global-sized Banks to have good and strong banking network to speed up economic growth.